Long-term outcomes in adult patients over 15 years of cochlear implant use - Our experience - Martins, Jorge Humberto (2014)
Objectives: In this study, the authors aimed to compare the performance of cochlear implant users with more and less than 15 years of cochlear implant experience.Material and Methods: Two groups were created: group 1 – 21 individuals with 15 or more years of cochlear implant experience; group 2 – 263 individuals with less than 15 years of cochlear implant experience. The instruments used were the tests that compose the evaluation protocol developed in the Otorhinolaringology Service of Centro Hospitalar Universitário de Coimbra – Hospital Geral.Results: The tonal audiometry results show statistically significant difference at 250, 4000 and 6000 Hz, with better results from group 1 (p<0.05). There was no statistically significant difference in vocal audiometry and in the following tests: monosyllables, numbers, sentences, vowels, consonants, 100 words and minimal pairs.Discussion and Conclusion: The results found are consistent with the international literature and show that the CI is a safe, reliable and long term efficient rehabilitation technique.